Map of North America : engraved to illustrate Mitchell's school and family geography. - Young, J. H. (James Hamilton) (S. Augustus Mitchell, 1839)
Map shows major cities and physical features for the United States; boundary line for a separate Texas which encompasses Santa Fe; pre-Gadsden Treaty border between U.S. and Mexico following the Gila River; Russian America [Alaska], British America, Mexico, Guatemala, the West Indies, and Greenland, and areas of Native American habitation. Relief shown by hachures. Scale [ca. 1:35,000,000].